Quentin Meillassoux and the Rehabilitation of the Principle of Sufficient Reason - Orensanz, Martín (2017)
Quentin Meillassoux has sparked new debates within contemporary philosophy. One of his suggestions is that the principle of sufficient reason leads to an infinite regress, unless the ontological argument uncovers a reason that accounts for everything. Graham Harman has indicated that the infinite regress of sufficient reasons that Meillassoux refers to does not necessarily lead to an absurd. A similar claim has been made by the proponents of infinitism for the infinite regress of propositions. It can be shown that the principle of sufficient reason does not need to be abandoned, and it is not necessary to accept the ontological argument either. Furthermore, the infinite regress of orders of facticity that Meillassoux refers to does not lead to an absurd. Instead, it suggests than facticity is not necessarily absolute. The consequence of this last point is that one does not need to accept the concept of the hyper-Chaos either.